Exploring science. 4 - Johnson, Penny; Levesley, Mark (Longman Harlow, 2005)
Primary Exploring Science Pupil Books are packed with real-life contexts, eye-catching photos, and informative diagrams that will keep children engaged and motivated in their science lessons.